Long‐term safety of certolizumab pegol in plaque psoriasis: pooled analysis over 3 years from three phase III, randomized, placebo‐controlled studies. (1st April 2021) - Blauvelt, A.; Paul, C.; van de Kerkhof, P.; Warren, R.B.; Gottlieb, A.B.; Langley, R.G.; Brock, F.; Arendt, C.; Boehnlein, M.; Lebwohl, M.; Reich, K.
Summary: Background: Certolizumab pegol (CZP) is an Fc‐free, PEGylated anti‐tumour necrosis factor biologic. Objectives: To report 3‐year safety data from three phase III trials of CZP in adults with plaque psoriasis. Methods: Data were pooled from CIMPASI‐1 (NCT02326298), CIMPASI‐2 (NCT02326272) and CIMPACT (NCT02346240). Included patients had moderate‐to‐severe plaque psoriasis of ≥ 6 months' duration; had been randomized to CZP 200 mg every 2 weeks (Q2W) (400 mg at weeks 0, 2 and 4) or CZP 400 mg Q2W; and had received at least one dose of CZP with up to 144 weeks of exposure. Treatment‐emergent adverse events (TEAEs) were classified using MedDRA v18·1. Reported incidence rates (IRs) are incidence of new cases per 100 patient‐years (PY). Results: Over 144 weeks, 995 patients received at least one dose of CZP (exposure: 2231·3 PY); 731 and 728 received at least one dose of CZP 200 mg Q2W (1211·4 PY) and/or 400 mg Q2W (1019·9 PY), respectively. The IR [95% confidence interval (CI)] of TEAEs was 144·9 (135·3–155·0) for all patients, 134·1 (123·2–145·7) for CZP 200 mg Q2W and 158·3 (145·5–171·9) for CZP 400 mg Q2W. The IR (95% CI) of serious TEAEs for all patients was 7·5 (6·4–8·8); the IRs were 6·7 (5·2–8·3) and 8·7 (6·9–10·8) for CZP 200 mg and 400 mg Q2W, respectively. Overall, 3·2% of patients reported serious infections (2·2% within each of the CZP 200 and 400 mg Q2W groups). Overall, there was one case of active tuberculosis, 16 malignancies in 14 patients and seven deaths (two considered treatment‐related). The cumulative IR of TEAEs did not increase over time. Conclusions: No new safety signals were identified compared with previously reported data. Risk did not increase with longer or higher CZP exposure.